<span> The answer
2 (x + 3) = 2x + 6</span>
Answer:
B -1/5
you have to follow pemdas first get rid of the parethase which leaves you with 2+3x+6x=-4x+8x+1 then you add what you can do then you get 2+9x=4x+1 then you subtract 2 from both sides and subtract 4x from both sides which leaves you with 5x=-1 then you divide 5 from both sides and get x=-1/5
12in=1ft
39/12=3.25ft
1m=3.25ft
times 4 both sides
4m=13ft
12ft
C
Answer:
c = 26 cm
Step-by-step explanation:
using the Pythagorean theorem:
10² + 24² = c²
c² = 100 + 576 = 676
c = 26 cm
Answer:
x = 32
Step-by-step explanation:
this is an equilateral triangle where all sides measure the same value; therefore, 2x-4 = 5y
since we are solving for 'x' we can set up this equation:
3(2x-4) = 180
6x - 12 = 180
6x = 192
x = 32